SUPERVISION AND PARTICIPATION IN TEACHERS WORKING GROUP TOWARD THE TEACH-ERS’ PROFESSIONAL COMPETENCE - Isniwati; Wahdini, Erny; Saleh, Muhammad (Journal of K6, Education and Management, 2019)
Learning activities cannot be carried out with optimum results in case teachers have professional competence. Academic supervision by the school principals and professional learning community activities are two of the efforts which are conducted to improve teachers? professionalism competence in Indonesia, especially in kindergarten level. This study aims at finding out the effect of school principal supervision and participation of the kindergarten teachers in Teacher Working Group (TWG), a kind of professional learning community, towards the kindergarten teachers? professional competence. There were 57 kindergarten teachers involved in this study. Data of the study were collected through questionnaire. The collected data from the result of the questionnaire were analyzed using multiple regression statistical analysis. Statistically, the results of the study show that academic supervision of quality achievement conducted by the school principals and teachers? participation in TWG have a significant effect on teachers? professional competence. For this reason, the following suggestions are made: (1) It is necessary for teachers to develop a positive mindset about the benefits of academic supervision; (2) teachers also need to actively participate in TWG activities; and (3) school principals needs to be closer to teachers.